2019
DOI: 10.1109/toh.2019.2941190
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Continuous and Pleasant Linear Sensations on the Forearm From a Sequential Discrete Lateral Skin-Slip Haptic Device

Abstract: A continuous stroking sensation on the skin can convey messages or emotion cues. We seek to induce this sensation using a combination of illusory motion and lateral stroking via a haptic device. Our system provides discrete lateral skin-slip on the forearm with rotating tactors, which independently provide lateral skin-slip in a timed sequence. We vary the sensation by changing the angular velocity and delay between adjacent tactors, such that the apparent speed of the perceived stroke ranges from 2.5 to 48.2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Through a user study, they found that users' sensations of continuity and pleasantness for the stroke stimuli could be maximized by increasing the driving duration and shortening the delay of each voice coil. Nunez et al [15] developed a device that uses rotating motors to present a sequential discrete lateral skin-slip sensation on the forearm. Through a user study, they found that their device can maintain continuity and pleasantness even at a large contact distance.…”
Section: Mediated Social Touch Devices For Stroking Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Through a user study, they found that users' sensations of continuity and pleasantness for the stroke stimuli could be maximized by increasing the driving duration and shortening the delay of each voice coil. Nunez et al [15] developed a device that uses rotating motors to present a sequential discrete lateral skin-slip sensation on the forearm. Through a user study, they found that their device can maintain continuity and pleasantness even at a large contact distance.…”
Section: Mediated Social Touch Devices For Stroking Presentationmentioning
confidence: 99%
“…Apparent tactile motion [52] is a tactile illusion in which a sequentially activated series of actuators makes a user believe that one actuator is moving along the skin. Although previous studies have applied this illusion to social haptic devices to reproduce a stroking sensation, they have displayed haptic information without synchronized visual information [14], [15], [16], [53], [54], [55]. Our arm-mounted device, however, is capable of the visuo-haptic presentation of stroking sensations by embedding activation signals in a hand image projected onto the user's forearm.…”
Section: Haptic Devices Controlled By Pvlcmentioning
confidence: 99%
See 2 more Smart Citations
“…al. evaluated affective response using rotating tactors and found speed and delay were factors in pleasantness ratings [Nunez et al 2019]. Further, Knibbe et.…”
Section: Background and Motivationmentioning
confidence: 99%